Podosome assembly is controlled by the GTPase ARF1 and its nucleotide exchange factor ARNO - Rafiq, Nisha Bte Mohd (J Cell Biol, 2017)
Podosomes represent a class of integrin-mediated cell-matrix adhesions formed by migrating and matrix-degrading cells. We demonstrate that in macrophage-like THP1 cells and fibroblasts stimulated to produce podosomes, down-regulation of the G-protein ARF1 or the ARF1 guanine nucleotide exchange factor, ARNO, by small, interfering RNA or pharmacological inhibitors led to striking podosome elimination. Concomitantly, treatments inducing podosome formation increased the level of guanosine triphosphate (GTP)–bound ARF1. ARNO was found to colocalize with the adhesive rings of podosomes, whereas ARF1 was localized to vesicular structures transiently contacting podosome rings. Inhibition of ARF1 led to an increase in RhoA-GTP levels and triggered assembly of myosin-IIA filaments in THP1 cells, whereas the suppression of myosin-IIA rescued podosome formation regardless of ARF1 inhibition. Finally, expression of constitutively active ARF1 in fibroblasts induced formation of putative podosome precursors: actin-rich puncta coinciding with matrix degradation sites and containing proteins of the podosome core but not of the adhesive ring. Thus, ARNO-ARF1 regulates formation of podosomes by inhibition of RhoA/myosin-II and promotion of actin core assembly.